Portal regional interactivo de las ciencias agrícolas: Plan parcial eje estratégico de innovación tecnológica agroindustrial Mosquera - Cundinamarca (2017)
In order to boost the agroindustrial competitiveness of the Savannah region of the West, this project proposes a level of partial plan, the design of a strategic district of agroindustrial technological innovation located in the Municipality of Mosquera, Cundinamarca, using urban strategies that improve the conditions of The region and the different land uses focused on science and technology, where projects are implemented that directly participate in the population and are led and financed mainly by the State through the presence of related institutions.